Sex and gender disparity in kidney transplantation: Historical and future perspectives. Issue 12 (26th September 2022) - Salas, Maria Aurora Posadas; Chua, Elizabeth; Rossi, Ana; Shah, Silvi; Katz‐Greenberg, Goni; Coscia, Lisa; Sawinski, Deirdre; Adey, Deborah
Abstract: Sex and gender disparity exist in various stages of kidney transplantation. Females were found to be less likely to be referred for kidney transplant, complete pre‐transplant evaluation, be placed on the waitlist, and receive a kidney transplant compared to their male counterparts. Interestingly, females comprise the majority of living kidney donors. This review explores the biological and psychosocial factors that contribute to sex and gender disparity in kidney transplantation and proposes ways to address the disparity.